The effect of female circumcision on maternal and neonatal outcomes after childbirth: a cohort study - Soheila Rabiepour; Zeynab Ahmadi (BMC, 2023)
Abstract Background Circumcision has many side effects and complications on women's lives and affects their physical, mental, and social health. The present study aimed to investigate the effect of female circumcision on maternal and neonatal outcomes. Methods Methods: A prospective cohort study was performed with 320 pregnant women by convenience sampling (160 individuals were circumcised and 160 were uncircumcised). Circumcision and its level were confirmed using observation. The data relating to demographic, midwifery history, medical history, maternal and neonatal outcomes were compiled using a questionnaire. All Statistical analyses were conducted by SPSS ver. 16.0. P-values less than 0.05 were considered significant. Results The mean age of circumcised women was significantly higher vs. Uncircumcised women (28.92±6.2 vs. 25.42±4.8; P < 0.001). Circumcision was significantly higher in rural compared to urban areas (51.9% vs.18.1%). The level of female education, his parents, spouse, and husband's employment status were significantly associated with circumcision (P < 0.001). 94.4% of uncircumcised nulliparous women and 86.9% of circumcised women experienced Intended Pregnancy (P=0.02). Eighty- five percent of women were circumcision type I. The higher mean duration of the second stage of labor, Second and Third degree of tear, and need for oxytocin in induction were significantly higher among circumcised women (P = 0.03, 0.003, 0.002, respectively). The existence one stage of labor, Second and Third degree of tear, and the need for oxytocin in induction were significantly higher among circumcised women (P = 0.03, 0.003, 0.002, respectively). Conclusion These findings underscore that Circumcision a prevalent predictor of poor neonatal outcomes and delivery processes, therefore this circumcised women needs intensive care during delivery.